Kebijakan Sistem Pemidanaan Dalam Upaya Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana - Rise Karmilia; Dani Kurniawansyah (Fakultas Hukum Universitas Pasir Pengaraian, 2022)
The policy of the criminal justice system based on the Diversion and Restorative Justice criminal justice system has been regulated in Law no. 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) prioritizes peace over the formal legal process. The essential changes include the use of a Restorative Justice approach through a diversion system. The purpose of this paper is to analyze and describe the implementation of the policy of the criminal system through restorative justice in Indonesia, especially related to the process of resolving criminal cases and to find out the legal efforts of rehabilitation through community mentors to foster children as perpetrators of criminal acts. This research is included as a normative legal research research using a study approach that examines the problems to be discussed using legal regulations in the form of secondary data (primary, secondary and tertiary legal materials). The analysis was carried out qualitatively and the discussion of the problem formulation using library research. This legal facility aims to anticipate the stigma caused when a child is in conflict with the law, as well as to restore and re-socialize the child. One solution is to divert or place the perpetrators of child crimes out of the criminal justice system and provide an alternative for settlement with a restorative justice approach with assistance carried out by community coaches.